Bimbingan penggunaan Bahasa Jerman praktis bagi pedagang di Kawasan Wisata Alam Bantimurung Kabupaten Maros - Misnah Mannahali; Nurming Saleh; Hasmawati Hasmawati; Mantasiah Mantasiah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Maros Regency is one of the districts in SouthSulawesi Province which has natural potential in the form ofbeautiful mountains, beaches, stretches of karst and exoticarchaeological sites. This potential makes this area rich innatural attractions and makes it one of the domestic andinternational tourist destinations. One tourist attraction that isvisited by tourists is Bantimurung natural tourism.Bantimurung tourist area is a prime tourist area in SouthSulawesi. As Bantimurung's mainstay tourist area, it offers avariety of interesting tourist attractions such as a flowingwaterfall, river flow with rocky edges flanked by steep cliffs,flying fox and also interesting is the attraction of butterflieswith various colors. This also caused Bantimurung to beknown internationally with the nickname